Speech Acts on Instagram comments about G20 Indonesia - Ahmadi F, Yusep; Syaifullah, Aceng Ruhendi; Hermawan, Budi (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2024)
Speech acts in someone's comments show a person's perception, interpretation and attitude towards something they read. This research aims to reveal the reading position in the comments of 3 posts on Instagram @indonesia.g20. The focus of this research is to describe the forms of comment speech acts on Instagram and show the reading position. The data source for this research has been the Instagram account @indonesia.g20 as the official Instagram account for the 2022 Indonesian G20 Presidency. This research method uses a mixed method. Comment data was analyzed using a speech act analysis framework and a reading position analysis framework. Quantitatively this research found 37 comments which included comments with 22% assertive speech act, 32% directive speech act, and 46% expressive speech acts. Meanwhile, reading positions based on performative speech acts include hegemonic reading position 62%, negotiated reading position 27%, and oppositional reading position 11%. Qualitatively it can be concluded that the comments on the 3 Instagram posts are positive comments in the form of expressive speech acts. This means that these commentators tend to like and support the implementation of the 2022 G20 Indonesia presidency on Instagram.